2020
DOI: 10.1083/jcb.201910177
|View full text |Cite
|
Sign up to set email alerts
|

Seipin and Nem1 establish discrete ER subdomains to initiate yeast lipid droplet biogenesis

Abstract: Lipid droplets (LDs) are fat storage organelles that originate from the endoplasmic reticulum (ER). Relatively little is known about how sites of LD formation are selected and which proteins/lipids are necessary for the process. Here, we show that LDs induced by the yeast triacylglycerol (TAG)-synthases Lro1 and Dga1 are formed at discrete ER subdomains defined by seipin (Fld1), and a regulator of diacylglycerol (DAG) production, Nem1. Fld1 and Nem1 colocalize to ER–LD contact sites. We find that Fld1 and Nem1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(125 citation statements)
references
References 48 publications
10
115
0
Order By: Relevance
“…4). These structures bear the hallmarks of early stages of LD assembly as they can be stained with Nile Red, are enriched in LD-localized proteins such as Erg6 and even recruit seipin, one of the earliest known factors that organizes LD biogenesis in the ER (Salo et al, 2019;Choudhary et al, 2020). These findings are interesting because they indicate that perilipins not only recognize cues that are specific to the monolayer of LDs but they also recognize possibly similar cues in the ER bilayer.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…4). These structures bear the hallmarks of early stages of LD assembly as they can be stained with Nile Red, are enriched in LD-localized proteins such as Erg6 and even recruit seipin, one of the earliest known factors that organizes LD biogenesis in the ER (Salo et al, 2019;Choudhary et al, 2020). These findings are interesting because they indicate that perilipins not only recognize cues that are specific to the monolayer of LDs but they also recognize possibly similar cues in the ER bilayer.…”
Section: Discussionmentioning
confidence: 92%
“…We have previously shown that Nem1 colocalizes with the LD biogenesis factor seipin at sites in the ER where neutral lipids are formed and LD biogenesis occurs (Choudhary et al, 2020). Given that the ER-crescents formed by the membrane proximal PLIN display hallmarks of sites of LD biogenesis, even in the absence of TAG and STE, we wondered whether seipin would also localize to these crescents.…”
Section: Wbp1-gfp-plin3 and Sec61-gfp-plin3 Form Crescent-like Er Dommentioning
confidence: 99%
“…Based on computational modeling, and evidence from in vitro and in vivo experiments, it has been shown that LD biogenesis also occurs at ER subdomains. [ 70–76 ] Importantly, the curvature and phospholipid asymmetry of the ER membrane appeared to determine the site and direction of LD emergence from the ER. Therefore, the preferential enrichment of specific proteins and lipids appear to be a central theme for ER‐LD engagement throughout the life cycle of LDs.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that seipin is a key player in early LD biogenesis and may define the ER subdomain primed for LD formation. Seipin foci are localized at LD forming sites in the ER during the earliest observable steps of LD biogenesis (Wang et al., 2016; Salo et al., 2019; Choudhary et al., 2020). Fluorescently labeled model ER-LD peptides harboring LD-targeting motifs, such as HPos and LiveDrop (Wang et al., 2016), have been used to visualize nascent LDs prior to their detection with traditional hydrophobic dyes such as BODIPY.…”
Section: Seipin Defines Ld Formation Sitesmentioning
confidence: 99%
“…While at least some of the PA-generating GPAT and AGPAT enzymes may have their active sites in the ER lumen or within the ER bilayer (Yamashita et al., 2014), the PA-utilizing lipin enzymes are soluble, cytosolic proteins (Zhang and Reue, 2017), which would necessitate PA flipping to access seipin. Intriguingly, there are indications that FIT2 might act as a lipid phosphate phosphatase in the ER luminal side (Hayes et al., 2017; Becuwe et al., 2018) and that the protein is localized at seipin-marked LD formation sites (Choudhary et al., 2020). In this scenario, seipin might function to trap PA to promote its efficient catalysis into DAG at the ER-LD contact.…”
Section: Seipin and Regulation Of Er Pl Metabolismmentioning
confidence: 99%